REGISTER BAHASA INGGRIS DALAM KOMPETISI MEMASAK MASTER CHEF INDONESIA SEASON 5 - Ferdian Achsani; Rustiya Ningsih; Lenggar Berryl Permana (Pusat Pengembangan Bahasa IAIN Tulungagung, 2020)
Register is one variation of language that arises because of the existence of certain social groups. This is because language always experiences development which cannot be seen when the language development occurs. The existence of social groups such as professional field does not rule out the possibility of creating a register. This study aims to describe the form of secret language codes or registers that often appear in the Master Chef Indonesia season 5 cooking. This research is included in the type of qualitative descriptive. Data and sources of data in this study are English words spoken either by the jury or the contestants, which are related to cooks or cooking. Data collection uses simat and note technique, that is by listening the use of English language registers on research objects, namely the Master Chef Indonesia season 5 impressions uploaded on youtube social networks. The results showed that there were forms of adjectives, nouns, verbs and adverbs in the spoken language used in the cooking competition. The existence of the phenomenon of the English register further adds to the vocabulary of the community, in bilingual mastery.